Dampak Penurunan Transfer ke Daerah terhadap Belanja Pegawai Kabupaten Jembrana - Veronika Nadia Andriyani (Journal of State Economic Research, 2025)
The Indonesian government plans to significantly cut Regional Transfers (TKD) by 24.7-29.34% in the 2026 Draft State Budget (RAPBN), from IDR 864.1 trillion to IDR 650 trillion. This study analyzes the impact of the TKD reduction on employee spending in Jembrana Regency, which has the lowest Regional Original Income (PAD) in Bali Province. Using a quantitative descriptive-analytical approach with 2024-2026 Regional Budget (APBD) data obtained from SIPD RI and the Ministry of Finance's DJPK Portal, this study maps the composition of employee spending and projects fiscal implications. The findings indicate that Jembrana's employee spending reached 38.78% of the APBD in 2026, far exceeding the maximum standard limit of 30% mandated by Law No. 1 of 2022. The 16.7% reduction in General Transfer Funds and the elimination of DAU allocations for PPPK salaries, education, and health create an acute fiscal dilemma. This study recommends a comprehensive strategy: imposing a moratorium on ASN recruitment, organizational restructuring, advancing digitalization, increasing PAD, and strengthening advocacy efforts to the central government.